An overview of numerical methods for modeling x-ray propagation through a multi-lens system - Szymon Tokarski; Paweł Wojda (TASK Quarterly)
This article offers a comprehensive examination of the field of X-ray optics and the methods employed to simulate X-ray propagation through multi-lens systems. The publication presents three distinct approaches to address X-ray optics problems, including the utilization of oriented Gaussian beams, the fast Fourier transform, and the second-order Runge-Kutta method. It also provides an in-depth analysis of the paraxial wave equation used in X-ray optics and how the paraxial approximation can be employed to reduce computational complexity. Finally, the article provides a detailed mathematical description of the concave lens used in X-ray focusing.